STIMULUS RESPONSE APPROACH USED BY THE TEACHERS IN TEACHING ENGLISH AT SMA NEGERI 5 ENREKANG - Yusmita; Ummi Khaerati Syam; Firman Firman (FKIP Unismuh Makassar, 2023)
This research aimed to find out the stimulus response used by the teachers and how do teachers provide stimulus to students in English learning at SMA Negeri 5 Enrekang.The method used in this research was descriptive qualitative. This research used a semi-structured interview as an instrument to collect the data. This research used ten questions as a data collection instrument. The subjects in this research were teachers of SMA Negeri 5 Enrekang. The research subjects consisted of three teachers.The result of this research show that teachers apply all types of stimulus in the teaching and learning process such as the application the law of readiness, the law of exercise, and the law of effect in English learning. Teachers apply the law of readiness to ensure the readiness of students in receiving material for example by checking student attendance. As for the application the law of exercises was used by teachers to ensure students’ understanding of the material that has been given, for example, by providing questions to be done individually, and the application the law of effect itself was used by teachers to reward students for what they achieved during the learning process, for example giving praise and good grades. The stimulus used was very beneficial to increase their learning motivation, especially in English Learning process.